Feasibility Assessment of Interactive Multimedia as an Innovation for Mathematics Learning in Elementary Schools - Sri Winarni; Muhammad Akhyar; Sudiyanto Sudiyanto (AL-ISHLAH: Jurnal Pendidikan, 2022)
Mathematics is a subject that is full of challenges and practical tasks that students must be able to do, this of course must be in line with the availability of various appropriate and innovative learning tools and resources which can then be used by students to deepen the material. Through research that aims to develop an interactive multimedia, it is hoped that it can become one of the appropriate learning media for students to use. This type of research is a Research and Development (RnD) method that adopts a 4D development model (Define, Design, Develop, Disseminate), with a focus on extracting data on Development (D) which contains an assessment of the feasibility of media products, with data collection techniques, namely non- test through a questionnaire, accompanied by a questionnaire instrument validation sheet. The data will be analyzed descriptively using percentage conversion in order to describe the feasibility of multimedia products. The results show that interactive multimedia that has gone through an assessment process from each evaluator with details, namely the assessment of media experts 90.1%, material expert assessments 83.3%, linguistic experts assessment 98%, media developer assessments 89.9% and assessment of elementary school teachers 97%. Through the results of the assessment, it can be concluded that the product of innovation in the form of interactive multimedia for learning in elementary schools is included in the category suitable for use as learning media